PENGARUH STRATEGI BISNIS PROSPECTOR TERHADAP KINERJA KEUANGAN YANG DI MEDIASI OLEH SISTEM INFORMASI AKUNTANSI MANAJEMEN PADA PERUSAHAAN JASA PERHOTELAN DI SURA - WIDYATMOKO WIBOWO, HARYO; , HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
This Research aimed to find the effect of prospector business strategy on financial performance, to determine the effect of prospector strategies on management accounting systems, to determine the effect of prospector business strategies on financial performance through management accounting information systems. this research is quantitative research. This study uses a type of primary data that is obtained from the distribution of questionnaires. The data obtained comes from large-scale especially in three-star and four-star hotels in Surabaya. The data analysis technique in this quantitative study uses statistics with the help of the Warp Partial Least Square (PLS) program. Partial Least Square (PLS). based on the results of the study, it was found that prospector strategies had a positive effect on financial performance, systems information management accounting, and financial performance directly. The prospector strategy also has a positive effect on financial performance partially by the management accounting information systemKeyword: prospector business strategy, financial performance, management accounting system information